Розвиток організаційно-економічних підходів до технічного переоснащення підприємств машинобудування - Бельтюков, Євгеній Афанасійович; Косенко, Олександра Петрівна; Петрович, Йосиф Михайлович (НТУ "ХПІ", 2016)
Розглянуто ефективні підходи до створення інтеграційних організаційно-економічних структур у сфері удосконалення технічного переоснащення виробництва вітчизняних промислових підприємств. Обґрунтовано, що ефективним підходом до підвищення темпів і якості технічного переоснащення виробництва може бути запропоновано здійснення технічного переоснащення виробництва на засадах інтеграції ресурсного потенціалу різних за своїми виробничими, інвестиційними та інноваційними потужностями підприємств, в тому числі у рамках Асоціації України з країнами Євросоюзу.

Considered effective approaches to integration of organizational and economic structures in the sphere of improvement of technical production re-equipment of domestic industrial enterprises. It proves that the motivation of the joint activity of two or more enterprises on a contractual basis is the need of strengthening the market competitive position, development of production and expand the range of innovative products, improving the technical and technological level of production, attraction of additional investments, integration of efforts in the areas of resource support, marketing and sales. The most effective option of joint activities is that, when each of the companies has a own pre-emptive resource that do not have other enterprises, only the integration of their resources into a coherent system provides the possibility of efficient production and marketing processes and achieve market synergies. It is substantiated that an effective approach to increase the pace and quality of the technical re-equipment of production can be the proposed implementation of the technical re-equipment of production based on the integration of the resource potential of their different industrial, investment and innovative capacity of enterprises, including in the framework of the Association of Ukraine with EU countries.
Development of organizational-economic approaches to technical reequipment of engineering enterprises
Keywords: промисловість; ресурси; конкурентоздатність; інвестиції; інновації; industry; competitiveness; investments; innovations